A renewable low-frequency acoustic energy harvesting noise barrier for high-speed railways using a Helmholtz resonator and a PVDF film. (15th November 2018) - Wang, Yuan; Zhu, Xin; Zhang, Tingsheng; Bano, Shehar; Pan, Hongye; Qi, Lingfei; Zhang, Zutao; Yuan, Yanping
Graphical abstract: Highlights: A novel noise barrier with a honeycomb structure was designed to harvest acoustic energy. The sound pressure was amplified in a Helmholtz resonator at a resonance frequency. A PVDF film was used to convert the energy of the sound resonance into electricity. The energy from the noise conversion was stored in supercapacitors to power small electronic devices. The tested properties are advisable for replacing a conventional noise barrier in high-speed rails. Abstract: High-speed railways have received much attention globally in recent years. While high-speed railways bring convenience to people, the environmental costs, such as noise pollution, are assignable, especially in residential areas near the railway. Notably, noise is a regenerative energy resource that can be harvested to generate electricity. Therefore, using noise barriers to simultaneously reduce noise and generate electricity is a meaningful research topic. In this paper, we present a novel renewable acoustic energy harvesting noise barrier using a Helmholtz resonator and a Polyvinylidene Fluoride (PVDF) film to convert the acoustic energy of low-frequency noise from high-speed railways into electricity. The renewable acoustic energy harvesting system scheme mainly consists of four components: a noise collection input module, a sound pressure amplification module, an electricity generator module and a power storage module. The sound pressure is amplified in a Helmholtz resonator, and a PVDF film in the electricity generator module can convert acoustic energy into electric energy. The power storage module stores the electric energy in supercapacitors that power small electronic devices, such as the monitors along the railway. Based on the experiments, one unit of the system can produce an instantaneous maximum output voltage of 74.6 mV at 110 dB (SPL), verifying the efficiency and practicability of the proposed acoustic energy harvesting noise barrier system being applied for renewable energy in high-speed railways.